DUKUNGAN ORANG TUA PADA ANAK DENGAN THALASEMIA - Murtini, Sri; Pradika, Jaka; Suriadi (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Thalassemia is a genetically inherited blood disorder that is chronic and difficult to prevent, significantly affecting children’s quality of life physically, socially, and emotionally. Improving quality of life requires not only medical management such as regular transfusions but also positive parental support, including motivation, attention, and nondiscriminatory treatment compared to healthy children. Understanding parental support and interaction is essential for promoting optimal outcomes. Purpose: This study aimed to assess the level of parental support and interaction for children with thalassemia. Methods: A descriptive study was conducted with purposive sampling, including 75 parents of children with thalassemia. Data were collected using structured observation sheets to evaluate parental support and interaction levels, alongside demographic information such as age, sex, education, and occupation. Results: Most respondents were aged 46–55 years (46.7%), female (86.7%), with high school education (53.3%), and homemakers (66.7%). Findings showed that 92.0% of parents provided positive support, and 78.7% demonstrated high interaction with their children. Positive parental involvement was observed in emotional support, attention to health needs, and daily engagement. Conclusion: Parents of children with thalassemia play a crucial role in providing positive support and interaction, contributing to the child’s overall well-being and recovery. Although this study was limited to survey-based observation, it highlights the importance of parental involvement in managing chronic pediatric conditions. Future research using qualitative approaches is recommended to explore in-depth parental experiences and validate these findings.